Inhibition of oil tea anthracnose by natural product extracts from Bacillus and Pseudoalteromonas isolates from mangrove soil - Liwang Fei; Liwang Fei; Liwang Fei; Xiaowen Xu; Jinying Feng; Lingyun Hao; Lingyun Hao (Frontiers in Marine Science, 2023)
This study investigates the potential of natural products derived from two mangrove soil bacteria, GP521A and GP3R5, in anthracnose management in oil tea. Based on 16s rDNA sequencing, GP521A and GP3R5 were identified as Bacillus velezensis and Pseudoalteromonas caenipelagi, respectively. Both bacteria showed strong antagonistic effects towards multiple fungal pathogens on dual cultural plates. The ethyl acetate extracts of fermentation cultures of GP521A (FEGP5) and GP3R5 (FEGP3) significantly inhibited mycelial growth of both Colletotrichum camelliae MC171, C. fructicola CF-1 and Pyricularia oryzae P131 at 100 and 200 μg/mL, respectively. Furthermore, FEGP5 and FEGP3 significantly inhibited conidiation, conidial germination and appressorial formation in C. camelliae MC171 at 50 μg/mL, with stronger inhibitory effects observed in the latter. On detached oil tea leaves, 100 μg/mL of FEGP5 and FEGP3 resulted in ~ 98.0% and 97.5% reduction in diseased areas, respectively, when applied before MC171 inoculation, whereas the reduction was approximately 55.0% and 77.6%, respectively, in the curative treatments. In fresh fruits, both extracts also significantly inhibited disease development, either in preventative or curative treatments. Moreover, FEGP5 and FEGP3 demonstrated significantly lower aquatic toxicity than prochloraz at the same concentrations towards a commonly used bioindicator, Artemia salina. In conclusion, this study demonstrates the potential of marine microbes derived natural products in development of environmentally compatible biopesticides to control anthracnose in oil tea.